To find the inverse Laplace transform of
\[
\frac{1}{2s^2 + 3s + 1}
\]
Step 1: Factor the quadratic expression in the denominator:
\[
2s^2 + 3s + 1 = (2s + 1)(s + 1)
\]
Step 2: Apply partial fraction decomposition:
\[
\frac{1}{(2s + 1)(s + 1)} = \frac{A}{2s + 1} + \frac{B}{s + 1}
\]
Step 3: Solve for \( A \) and \( B \):
Multiplying both sides by \((2s + 1)(s + 1)\) and equating coefficients gives:
\[
1 = A(s + 1) + B(2s + 1)
\]
Solve for \( A = 1 \) and \( B = -1 \).
Step 4: Write the expression:
\[
\frac{1}{(2s + 1)(s + 1)} = \frac{1}{2s + 1} - \frac{1}{s + 1}
\]
Step 5: Take the inverse Laplace transform:
\[
\mathcal{L}^{-1} \left( \frac{1}{2s + 1} \right) = e^{-t/2}, \quad \mathcal{L}^{-1} \left( \frac{1}{s + 1} \right) = e^{-t}
\]
Thus, the inverse Laplace transform is:
\[
e^{-t/2} - e^{-t}
\]
Conclusion:
The correct inverse Laplace transform is given by option (A).